Business model adaptation in market fluctuation : a study of Vietnamese travel companies - Doan, Truc (2018)
Business model concept has developed over time since the 70s. Among all the company types, SMEs are accounted for the majority of the Vietnamese tourism sector. In this thesis, the author would like to analyze how the SMEs tourism case companies adapt their